Pleasure and power in Nazi Germany - Swett, Pamela E. 1970- Hrsg; Ross, Corey 1969-; Almeida, Fabrice d' 1963- (Palgrave Macmillan, 2011)
"Although we associate the Third Reich above all with suffering, pain, and fear, pleasure played a central role in its social and cultural dynamics. This book explores the relationship between the rationing of pleasures as a means of political stabilization and the pressure on the Nazi regime to cater to popular cultural expectations"--